Why Is the Healing of Emotional Problems So Difficult? - Friesel, Hillel Zvi (Homeopathy, 2019)
Background This article deals with the difficulties involved in the healing of emotional problems. It focuses on the homeopathic treatment combined with other therapeutic approaches.Findings In working with emotional problems, homeopathy focuses mainly on the action of the homeopathic medicine. Arguably, it over-relies on the healing power of the medicine and gives less attention to the importance of working dynamically with the patient's emotional problems. This article suggests a more balanced approach that combines between these two facets of the healing process, giving more weight to the role of potencies.Conclusion Emotional healing becomes more plausible when the patient's inner strength attains the level of strength of the disturbance, represented by “level of potency”, which allows the patient to cope with his/her disturbance more successfully.
Keywords: potency; strength of disturbance; strength of patient; emotional healing